Studies in stemmatology - Reenen, Pieter Th. van (John Benjamins Pub. Co., 1996)
This volume contains ten papers selected from among those presented at the annual Free University Stemmatological Colloquia 1990-93. Current issues in (automated) stemmatology, paleography and codicology are addressed from contemporary theoretical perspectives. All papers focus on new directions in textuology and manuscript affiliation, and especially on the use of computer science in this field. The theoretical implications of computer-assisted stemma construction are explored. In combination with achievements in codicology and paleography, these investigations allow for dealing with the major.